ANALYSIS OF CHARACTERISTIC NEWS CONTENT AND ACCURACY IN ONLINE JOURNALISM (Rape Case by Reynhard Sinaga on Tirto.id News Portal) - Maghrifi, Icha Rochmah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Abstract: The development of information and communication technology is marked by the increasing use of online media. The presence of the internet that is used as the Internet of Things (IoT) or the Internet for Everything makes people more often use the internet, especially in meeting their needs, one of the needs of fulfilling information. Online journalism is one of the latest breakthroughs in the world of journalism that can fulfill information for the public through the internet. However, online journalism is often regarded as a news media that is fixed at one point of necessity, namely speed. The inevitability of online journalism is often in the spotlight because it is considered to sacrifice the basic principles of journalism, especially the accuracy of news for the sake of speed. In connection with the Reynhard Sinaga case which is quite complicated, and has just appeared in the media including Tirto.id. Therefore this research formulates the problem and aims to find out: (1) news characteristics of the Reynhard Sinaga case in the Tirto.id portal and (2) the accuracy level of the news of the Reynhard Sinaga case in the Tirto.id news portal. This research uses descriptive research with a descriptive quantitative approach, which analyzes the characteristics and accuracy of news related to the Reynhard Sinaga case in the portal Tirto.id. Researchers get the data of news from the documentation directly in the Tirto.id website. The results of this study conclude that (1) the news characteristics of the Reynhard Sinaga case in the Tirto.id portal are in accordance with theories relating to the characteristics of online journalism which always emphasizes the important principle of immediacy or freshness of news and multimedia or the diversity of formats in news delivery. (2) the accuracy of the news published by Tirto.id which is assessed from 5 categories of accuracy assessment shows that the news contained in the portal can be considered accurate. With an accuracy value above fifty percent.